PRAKTEK KERJA INDUSTRI RELEVANSINYA TERHADAP DAYA SERAP KERJA SISWA LULUSAN SMK PROGRAM KEAHLIAN PENJUALAN - Feri Agustiani, (Pendidikan Ekonomi, 2010)
The objectives of the present research are to investigate (1) the implementation of  internship, (2) employability of the graduates of the sales major, and (3) relevance of internship and the occupations of the graduates. The sample of the study was 164 students in SMKN I Boyolangu.  The data were collected with observation, interview and documentation.  The data were then analyzed descriptively. The findings of the study show that the implementation of the internship has run well. In terms of employability of the graduates of the sales major in academic year 2006-2007 and 2007-2008, 1.83 % the graduates worked in governmental agency,  5. 49 % became entrepreneurs,  51.83 %  worked in the field relevant with their internship, 10.98% worked as employees at private sectors, 7.32 %  pursued higher education, and 22.56 % got married.  It was also revealed that there was a relevance between the internship and the graduates occupations in which 51.83 % of the graduates worked in the similar field with internship.